Post-mortem tissue biopsies obtained at minimally invasive autopsy: an RNA-quality analysis. - Anita van der Linden; Britt M Blokker; Marcel Kap; Annick C Weustink; Jan L Robertus; Peter H J Riegman; J Wolter Oosterhuis (PLoS ONE, 2014)
Introduction Bereaved relatives often refuse to give consent for post-mortem investigation of deceased cancer patients, mainly because of the mutilation due to conventional autopsy (CA). Minimally invasive autopsy (MIA) may be a more acceptable alternative and, if implemented in clinical practice, creates an opportunity to more often obtain post-mortem tissue samples of (recurred) primary tumors and metastases for molecular research. As a measure for tissue quality for molecular studies, we hereby present a feasibility study, comparing the RNA quality of MIA and CA samples, and fresh frozen samples as reference. Materials and methods Tissue samples of heart, liver and kidney were prospectively collected from 24 MIAs followed by CA, and compared to corresponding archival fresh frozen tissue. After RNA isolation and RT-qPCR, RNA integrity numbers (RIN) and GAPDH expression (six amplicon sizes ranging from 71 to 530 base pairs) were measured. RIN values and GAPDH Cq values were analyzed and compared between all sample groups and post-mortem intervals (PMI). Results RIN values in MIA samples were significantly higher than those in CA samples. GAPDH was expressed significantly higher in MIA samples than in CA samples and 530 bp PCR products could be measured in all cases. GAPDH expression was significantly lower in samples with PMI >15 hours. As expected, the samples of the fresh frozen reference standard performed best in all analyses. Conclusion MIA samples showed better RNA quality than CA samples, probably due to shorter PMI. Both had lower RNA quality and expression levels than fresh frozen tissue, however, remaining GAPDH RNA was still sufficiently intact. Therefore, other highly expressed genes are most likely also detectable. Gene array analysis should be performed to gain insight into the quality of entire post-mortem genomes. Reducing PMI will further improve the feasibility of demanding molecular research on post-mortem tissues, this is most likely more feasible with MIA than CA.